2015
DOI: 10.1016/j.rhm.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for routine episiotomy: A mixed-methods study in a large maternity hospital in Phnom Penh, Cambodia

Abstract: First documented in 1741, the practice of episiotomy substantially increased worldwide during the 20th century. However, research shows that episiotomy is not effective in reducing severe perineal trauma and may be harmful. Using a mixed-methods approach, we conducted a study in 2013-14 on why obstetricians and midwives in a large maternity hospital in Phnom Penh, Cambodia, still do routine episiotomies. The study included the extent of the practice, based on medical records; a retrospective analysis of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 24 publications
7
33
3
6
Order By: Relevance
“…13 Damage during vaginal birth has recently been observed in Phnom Penh where routine episiotomy is practiced in order to "help" women deliver faster. 27 Lumbiganon and colleagues have shown that women often do not know that, when performed without medical justification, this surgical intervention may increase maternal and perinatal morbidity, causing an unnecessary additional health burden. 2 In our study, many women mentioned that they felt a c-section would be safer for their baby and themselves.…”
Section: Discussionmentioning
confidence: 99%
“…13 Damage during vaginal birth has recently been observed in Phnom Penh where routine episiotomy is practiced in order to "help" women deliver faster. 27 Lumbiganon and colleagues have shown that women often do not know that, when performed without medical justification, this surgical intervention may increase maternal and perinatal morbidity, causing an unnecessary additional health burden. 2 In our study, many women mentioned that they felt a c-section would be safer for their baby and themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many harms of episiotomy, however, episiotomy remains a very common practice among Chinese populations with reported incidences of 82%, 86%, and 100% in Mainland China, Hong Kong, and Taiwan, respectively, and routine use of episiotomy for nearly all first vaginal births in China . Internationally, there is a wide variation in episiotomy rates, varying from as low as 6.7% (Hawaii) to as high as 94.5% (Cambodia) . There are no valid guidelines for the performance of episiotomy, and the decision of the procedure is based on clinical judgment of the accoucheur attending the delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Episiotomy is the birth interventions that commonly performed to enlarge the perineum during delivery which, may be justified for specific maternal or fetal indications such as poor maternal effort, forceps extraction or fetal distress, however, the routine use of this procedure is being questioned [3,21]. The World Health Organization (WHO) has recommendation to restrict the use of episiotomy procedure in low risk pregnancy, nevertheless, this procedure has remained constant in all countries around the world [5,11] in particular developing countries [3,5,21].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) has recommendation to restrict the use of episiotomy procedure in low risk pregnancy, nevertheless, this procedure has remained constant in all countries around the world [5,11] in particular developing countries [3,5,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation